1968
DOI: 10.1083/jcb.37.1.27
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Stereological Description of the Ultrastructure of Normal Rat Liver Parenchymal Cells

Abstract: The principles of stereology have been applied to a morphometric analysis of parenchymal cells from the peripheral, midzonal, and central regions of normal rat liver lobules. The fractional volumes of cytoplasm occupied by mitochondria, peroxisomes, lysosomes, lipid, and glycogen have been determined. The surface densities of smooth-and rough-surfaced endoplasmic reticulum and of mitochondrial envelope and cristae have also been measured. The average number and dimensions of mitochondria and peroxisomes have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
260
5
6

Year Published

1972
1972
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 688 publications
(294 citation statements)
references
References 32 publications
23
260
5
6
Order By: Relevance
“…This analysis of model systems has shown that some of the previous concepts of section thickness effects have had to be revised. Loud (21) had reasoned that membrane systems such as cisternae of ER or mitochondrial cristae should be underestimated, because the difficulty of recognizing obliquely sectioned elements should lead to a "loss" of up to 1/3 of the membrane; in an earlier study from this laboratory (35), this concept was adopted although the loss was considered somewhat less important. This notion must be revised: First, considerations on the geometric probability of sectioning have revealed grazing sections of ER cisternae or cristae to be relatively rare events; secondly, the use of en bloc staining with uranyl acetate enhances the contrast so that obliquely sectioned membranes are still recognized to a large extent particularly if the analysis is done at high magnification, as in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…This analysis of model systems has shown that some of the previous concepts of section thickness effects have had to be revised. Loud (21) had reasoned that membrane systems such as cisternae of ER or mitochondrial cristae should be underestimated, because the difficulty of recognizing obliquely sectioned elements should lead to a "loss" of up to 1/3 of the membrane; in an earlier study from this laboratory (35), this concept was adopted although the loss was considered somewhat less important. This notion must be revised: First, considerations on the geometric probability of sectioning have revealed grazing sections of ER cisternae or cristae to be relatively rare events; secondly, the use of en bloc staining with uranyl acetate enhances the contrast so that obliquely sectioned membranes are still recognized to a large extent particularly if the analysis is done at high magnification, as in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…The principles involved in the quantitative, stereological, or morphometric analysis of tissues have been described recently (3,4) . The fraction of tissue volume occupied by component i (V" ') is proportional to the fraction of the area (of a thin section) occupied by this component .…”
Section: The Methods Of Morphometrymentioning
confidence: 99%
“…Several enzymes which emerge during late fetal or neonatal life remain constant per gram (i .e ., increase per cell) during the postnatal doubling of the parenchymal cell volume (e .g ., glycogen synthetase, tyrosine aminotransferase, and glucokinase in Figs . [4][5][6], suggesting that they are concerned with the maintenance of cytoplasmic functions . On the other hand, enzymes which are high in fetal liver and may be necessary for proliferation might be expected to remain low per cell after the establishment of minimal rates of mitosis .…”
Section: The Bases Of Expressing Enzyme Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The size of the midzonal hepatocytes before and after PCS were determined by tracing large numbers of liver cells on standard thickness paper, cutting out the silhouettes, and weighing them (9). Midzonal hepatocytes identified in half-micron Epon sections were also used for measuring on electron micrographs the area of rough and smooth endoplasmic reticulum within these cells and the dimensions of mi- (15). Autoradiography was performed on dewaxed paraffin sections of liver using Ilford K2 nuclear emulsion.…”
Section: Pathologic Studiesmentioning
confidence: 99%